ANALISIS KERJASAMA PENANGANAN PENGUNGSI UNI EROPA-TURKI PASCA RUNTUHNYA REZIM BA’ATH SURIAH - D'Novaliano, Ryvo (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
Conflict-induced immigration has long been a humanitarian crisis not only in the countries where conflicts occur, but also in neighboring countries where refugees are fleeing. The Arab Spring uprisings spread to Syria, prompting demonstrations that were responded to excessively by security forces. Armed military forces were deployed to contain the wave of protests against the government, using repressive measures that resulted in the loss of many lives. The protests quickly spread across Syria and transformed into a civil war with external parties intervening. In a dangerous conflict situation, the Syrian population began to migrate out of the country. Turkey became the main destination for refugees as a place to stay and a stopover route before going to Europe. The wave of migration caused a refugee crisis in the European Union. Finally, the European Union took a step to cooperate in handling refugees with Turkey, the refugees will be placed in Turkey, while the European Union will reconsider Turkey's membership in the organization and provide financial assistance. The end of the Ba'ath party's rule in Syria signaled the end of the prolonged civil war and paved the way for refugees to return to their home countries. This will certainly affect the cooperation between Turkey and the European Union as the refugee crisis in the country decreases. Keywords: Turkey, European Union, Refugee Crisis